(untitled) (Journal of Philosophy Culture and Political Science, 2018)
In this article the author investigates a success phenomenon from the point of view of presence at it of a social and estimated factor. Reflections of the author are defined by studying of a ratio of internal personal estimated criteria and criteria of social approval and recognition. Estimating different scientific searches of success the author stops on the concept of the «self-updating» offered by Abraham Maslou in more detail. The author estimates positive and negative sides of this concept. The main conclusion of the author is connected with judgment of the nature of self-development. Key words: success, development, self-realization, life strategy, perfection, values.